The use of intra-aortic balloon pump in cardiac surgery - Alqudah, Bashar; Alshobaki, Wael; Alghawanmeh, Suhaib; Abuamira, Hamza; Alhrahsheh, Hamzeh A.; Alsharo, Sakher A.; Mohd, Ashraf F. (International Journal of Advances in Medicine, 2024)
Background: Objective of the study was to determine the incidence of use, indications, complications of intra-aortic balloon pump (IABP) and its impact on outcome. Methods: Retrospective study of adult cardiac surgical patients presenting for cardiac surgery at Queen Alia Heart Institute in the period of time between September 2023 and February 2024. Patients’ demographic, clinical, perioperative data were recorded and analysed. Time of initiation of intra-aortic balloon, indications and monitoring for complications were observed by the authors. Patients were divided into two groups according to the use of IABP; the IABP group and the non-IABP group. Both groups were compared regarding outcome. Ethical committee approval obtained. Results: Data from 202 adult cardiac surgeries was analysed. Average age of patients was 57.2 years. Patients were 34 females (16.8%) and 168 males (83.2%). Most surgeries were elective (93.6%), while urgent surgeries comprised 3.5% and emergency surgeries were 3%. Coronary artery bypass grafting (CABG) was the most common procedure (78.2%). The IABP was most commonly used after combined procedures (50%) and to a lesser extent after isolated CABG (15.3%). IABP was inserted least frequently pre-operatively (10.7%), followed by postoperative insertion (35.7%), while intraoperative insertion to aid weaning from CPB was most common (53.6%). Patients from the IABP group were older, had longer CPB time (136.7 minutes) and AXC times (70.5 minutes), they also spent around 2 days more in the ICU and around 4 days more in hospital. Conclusions: IABP was most commonly utilised for combined procedures, after prolonged CPB and aortic cross clamping. The use of IABP was associated with delayed tracheal extubation, longer ICU stay, longer hospitalisation, and higher rates of blood transfusion, higher incidence of re-opening and higher mortality.